Construction Research Congress 2012 2012
DOI: 10.1061/9780784412329.175
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Green-Roof on Reducing Energy Consumption through Simulation Program for a Residential Building: Cairo, Egypt

Abstract: Green-roofs are becoming a popular breathing roofing alternative to traditional roofing systems. Green-roofs were mentioned as an ecological-economical solution; however, limited work has been carried out on the potential life cycle cost savings of green roofs in arid climates. This paper present costs savings by green roofs in arid climates. The model accounts for energy savings, structural considerations as well as other variables. Detailed thermal simulations for various configurations of green roofs are pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…In addition, higher soil thermal conductivity was found to be more efficient in improving the cooling process than the lower soil thermal conductivity. This finding is consistent with that in previous studies [34][35][36] that shows that a higher soil thermal conductivity in the green roof combined with an increased moisture content in the soil contributes to an increase in the evaporation rate, thus reducing the heat flow within the interior spaces. It might, therefore, be concluded that the cooling effectiveness in the building bears a negative relationship with the soil depth that is associated with a high LAI and a positive relationship with the soil thermal conductivity of the green roof.…”
Section: Evaluation Of Annual Energy Consumptionsupporting
confidence: 93%
“…In addition, higher soil thermal conductivity was found to be more efficient in improving the cooling process than the lower soil thermal conductivity. This finding is consistent with that in previous studies [34][35][36] that shows that a higher soil thermal conductivity in the green roof combined with an increased moisture content in the soil contributes to an increase in the evaporation rate, thus reducing the heat flow within the interior spaces. It might, therefore, be concluded that the cooling effectiveness in the building bears a negative relationship with the soil depth that is associated with a high LAI and a positive relationship with the soil thermal conductivity of the green roof.…”
Section: Evaluation Of Annual Energy Consumptionsupporting
confidence: 93%
“…All simulations will implement a green roof and wall (100% coverage), then, will compare it with a base case (bare wall). A 15cm soil thickness (extensive) is set for any green layer (roof or wall), as it is the most efficient thickness in arid climates [43], Table 2 present the properties of any green layer used in the simulation. Building systems and materials description in DesignBuilder are presented in Table 3…”
Section: Scenarios Setupmentioning
confidence: 99%
“…Another model with two stories residential building in Cairo, Egypt with a base case control which uses a traditional roof that meets standard model energy code was simulated while changing the conductivity and the thickness of the green-roof soil. The results showed that savings varied from 15-32% compared to traditional and un-isolated roofs [16]. Other study by Issa Jaffal, Salah-Eddine Ouldboukhitine and Rafik Belarbi, aims to provide a comprehensive study of the influence of a green roof on building energy performance.…”
Section: Literature Reviewmentioning
confidence: 99%